1995
DOI: 10.1128/aac.39.5.1087
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in reverse transcriptase of human immunodeficiency virus type 1 reduce susceptibility to foscarnet in laboratory and clinical isolates

Abstract: Foscarnet (phosphonoformic acid) is a pyrophosphate analog that inhibits the replication of human immunodeficiency virus type 1 (HIV-1) in vitro and in patients with AIDS. HIV-1 resistance to foscarnet has not been reported despite long-term foscarnet therapy of AIDS patients with cytomegalovirus disease. We therefore attempted to select foscarnet-resistant HIV-1 in vitro by serial endpoint passage of virus in 400 M foscarnet. After 13 cycles of passage in MT-2 cells, virus exhibiting Ն8.5-fold foscarnet resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 33 publications
5
83
0
Order By: Relevance
“…With few exceptions, many of these mutations are too far away from the active site to affect the interaction with the dNTP or nucleic acid substrate directly (8). The W88G change is perhaps the most prevalent mutation that is found in clinical isolates (7). Crystallographic data suggest that a change at the adjacent position, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With few exceptions, many of these mutations are too far away from the active site to affect the interaction with the dNTP or nucleic acid substrate directly (8). The W88G change is perhaps the most prevalent mutation that is found in clinical isolates (7). Crystallographic data suggest that a change at the adjacent position, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In this context it is also important to note that template position ϩ5 is associated with intrinsic pausing of RT at limiting dNTP concentrations, which is in keeping with the observation that the stability of the post-translocated complex is likewise diminished. The selective pressure of PFA can cause the emergence of resistance conferring mutations in the RT gene in vitro and in vivo (7,9). With few exceptions, many of these mutations are too far away from the active site to affect the interaction with the dNTP or nucleic acid substrate directly (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (8) demonstrated that mutations that confer resistance to dideoxynucleoside analogues, including L74--V, apparently lead to changes at the active site through changing the conformation or position of the template-primer. Analyses of foscarnet-resistant HIV-1 RT also suggest that mutations across the DNA-binding cleft may lead to alterations in binding of foscarnet at the polymerase active site, again "communicating" from the site of mutation through the template-primer (26). We therefore propose a connection between quinoxaline-specific mutations that impair polymerase activity and the NRTI mutations that occur in the fingers subdomain.…”
Section: Analysis Of the Hiv-1 Rt Gene During In Vitro Selection Formentioning
confidence: 99%
“…The low fidelity of retroviral replication is a major force for generation of high levels of variation in retroviral populations (8), which allows them to adapt quickly to changes in their environment. One important outcome of this high adaptability is the rapid development of resistance to antiretroviral drugs and escape from host immune responses (9). Mutations that occur in retroviruses during replication include substitutions, frameshifts, deletions, duplications, and hypermutations (10,11).…”
mentioning
confidence: 99%